Russia-China economic relations: Moscow's road to economic dependence - Janis Kluge (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia's full-scale invasion of Ukraine has fundamentally changed the terms of Russia-China economic relations. Economic cooperation with China has become vital for the Russian economy. Trade turnover between Russia and China has increased significantly since February 2022. However, Chinese companies remain hesitant about investing in Russia. Energy cooperation remains the backbone of Sino-Russian cooperation, but the expansion of Russian exports is hindered by infrastructure limitations. Russian arms exports have declined in recent years. Meanwhile, China exports large quantities of dual-use goods to Russia, which are urgently needed by the Russian military industry. Sino-Russian cooperation in the digital economy has been hit hard by Western sanctions. China's digital giants cancelled several projects in Russia due to fears of secondary U.S. sanctions. Russia's trade with China is mainly conducted in Chinese yuan. However, Russia continues to rely on the U.S. dollar for trade with the rest of the world.
Keywords: 320; Russia-China economic rlations; invasion of Ukraine; energy cooperation; arms exports; dual-use goods; Russian military industry; digital economy; yuan; U.S. dollar